Glencoe science : - Blaustein, Dan (Glencoe/McGraw-Hill, 1999)
This book includes 3 units and 18 chapters: Unit 1: Life science: What is life?, Cells, Heredity and reproduction, Diversity and adaptations,...; Unit 2: Physical science: What is matter?, Properties and changes, Forces and motion,...; Unit 3: Earth science: The solar system and beyond, Earth materials, Earth's structure, Water,...